The effect of carotene extraction system on crude palm oil quality, carotene composition, and carotene stability during storage - Baharin, B. S.; Latip, R. A.; Che Man, Y. B.; Abdul Rahman, R. (Wiley, 2001)
Palm carotene was successfully concentrated from crude palm oil (CPO) by an adsorption process using a synthetic adsorbent followed by solvent extraction. Evaluation of feed CPO and CPO which underwent the carotene extraction process was conducted. The quality of CPO after the extraction process was slightly deteriorated in terms of free fatty acid, moisture content, impurities, peroxide value, anisidine value, discriminant function, and deterioration of bleachability index. However, the CPO still can be refined to produce refined, bleached, deodorized palm oil that meets the Palm Oil Refiners Association of Malaysia specifications. No extra cost was incurred by refining this CPO as the dosage of bleaching earth used was very similar to the refining of standard CPO. The triglyceride carbon number and fatty acid composition of CPO after going through the carotene extraction process were almost the same as CPO data. The major components of the carotene fraction were similar to CPO, which contains mainly α‐ and β‐carotene. The carotene could be stored for at least 3 mon.